2002
DOI: 10.1074/jbc.m110249200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of the Human Diacylglycerol Kinase β (DGKβ) Gene

Abstract: Diacylglycerol kinases are key modulators of levels of diacylglycerol, a second messenger involved in a variety of cellular responses to extracellular stimuli. A number of diacylglycerol kinases encoded by separate genes are present in mammalian genomes. We have cloned cDNAs encoding several isoforms of the human homologue of the rat diacylglycerol kinase ␤ gene and characterized two such isoforms that differ at their carboxyl terminus through alternative splicing and the usage of different polyadenylation sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…In the case of DGK2, the alternative splicing appears to alter its inhibitory effects on Ras guanyl nucleotide-releasing protein and subcellular localization (27). DGK␤ isoforms differ from each other at their C termini through alternative splicing and one variant was associated with the plasma membrane, whereas the other isoform was predominantly localized in the cytoplasm (24). Therefore, alternative splicing may be a common mechanism in regulating DGK functions in different tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of DGK2, the alternative splicing appears to alter its inhibitory effects on Ras guanyl nucleotide-releasing protein and subcellular localization (27). DGK␤ isoforms differ from each other at their C termini through alternative splicing and one variant was associated with the plasma membrane, whereas the other isoform was predominantly localized in the cytoplasm (24). Therefore, alternative splicing may be a common mechanism in regulating DGK functions in different tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…occurrence of alternative splicing in multiple DGK genes further supplements the complexity of the DGK gene family members, and apparently contributes to fine-tuning the action of DGKs regulating a wide range of cellular functions. Indeed, in the case of DGK␤, the control of the alternative splicing of this gene is hypothesized to be involved in the pathogenesis of human mood disorders (24).…”
mentioning
confidence: 99%
“…In fact, Caricasole et al (15) have reported recently that human-DGK␤ was redistributed from the cytoplasm to the plasma membrane of HEK-293 cells upon TPA treatment. However, we could not confirm this translocation in our assay system using CHO-K1 cells because almost all GFP-DGK␤ exists in the plasma membrane and not in the cytoplasm (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…To date, nine subtypes of mammalian DGKs have been cloned (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). All DGK isozymes consist of a conserved catalytic domain and two or three cysteine-rich C1 domains designated as C1A, C1B, and C1C (16).…”
mentioning
confidence: 99%
“…Deletion of this C-terminal region greatly alters plasma membrane localization of this isoform in vivo (27). Sequence analysis of the C-terminal sequence of type I enzymes indicated conservation of a Pro-rich sequence followed by an amino acid stretch with no obvious conservation among distinct subtypes (Fig.…”
Section: Deletion Of the Dgk␣ C-terminal Region Prevents Constitutivementioning
confidence: 99%